“MATHEMATICS ACHIEVERS IN ALBAY: STORIES OF SUCCESS AND CHALLENGES” - Nasayao, Maria Tricia B.; Goyena, Jocelyn F. (PEOPLE: International Journal of Social Sciences, 2020)
Most students fear Mathematics but still some manage to excel in the subject. This study referred to those students as the Mathematics achievers. Life stories of seven Albayano Mathematics achievers were written. They exemplify “best” in joining competitions regionally, nationally, and internationally. The narratives highlight their personal and socioeconomic background, achievements and success stories, challenges and coping mechanisms, and contributing factors to success: preparation, support system and motivation. The insights drawn from the achievers’ narratives may inspire excellence in Mathematics and served as basis for the development of an enrichment program. Class observations and interviews were conducted to answer the sub-problems. The stories were content organized and analyzed to find commonalities and uniqueness in achievers, verbatim quotations were also integrated. Findings showed that opportunities to join competitions were based on the efforts of coach/es, priorities of schools, and the community. Both genders were good in Mathematics and were dominantly visual learners. Their study habits were grounded on their learning styles and multiple intelligences. The type of family they were in, source of living, number of siblings, and the families’ average monthly income were analyzed. Financial problem and anxiety were the mutual challenges they had. The achievers were intrinsically and extrinsically motivated. Greater number of coaches for longer review time assure better competition performance. The schools’ motive of maintaining good performance and gaining/regaining trust, and coaches’ purpose of showcasing talents for professional growth and satisfaction open opportunities for public high school students with the abilities and confidence to join and win Mathematics competitions.